ChemInform Abstract: Pd‐Catalyzed Cross‐Coupling Reactions of Arenediazonium Salts with Arylsilanes and Aryltrifluoroborates in Water. Issue 12 (25th March 2014) - Cheng, Kai; Zhao, Baoli; Hu, Sai; Zhang, Xian‐Man; Qi, Chenze
Abstract It is demonstrated that arenediazonium tetrafluoroborates can efficiently be used in Pd‐catalyzed Hiyama as well as Suzuki—Miyaura cross‐coupling reactions to produce a series of biphenyl derivatives.